2008
DOI: 10.1108/03699420810887861
|View full text |Cite
|
Sign up to set email alerts
|

A novel natural adhesive from rice bran

Abstract: Purpose -The purpose of this paper is to investigate a new approach for making a bio-based adhesive from a new resource, rice bran (RB) adhesive. Design/methodology/approach -RB solution was prepared and its pHs were adjusted to either 8.5-9.0 or 10.0-10.5. The solid content of slurry was controlled at <18 per cent and then gelatinised in a water bath shaker at 608C for 2 h or at 1008C for 1 h. The bonding strength of RB adhesive was determined by testing the strength of three-layer plywood. A differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Natural adhesives were used a lot before the1930's, and then, they have been almost entirely replaced by synthetic adhesives (Wang et al 2008). However, wood adhesives from renewable raw materials have been a topic with considerable interest for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Natural adhesives were used a lot before the1930's, and then, they have been almost entirely replaced by synthetic adhesives (Wang et al 2008). However, wood adhesives from renewable raw materials have been a topic with considerable interest for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Without modification, starch was used as a binder in their native form by Ozemoya et al [16], Wang et al [17], and D'Amico et al [18]. Some modification trial was done to produce carbamoyl ethylated starch through acrylamide to modify corn starch.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the interactions between the two polymers in solution were closely related to the mechanical properties of the biomaterial formed 6. All these bioadhesives have been traditionally used for many years, but have been gradually superseded by synthetic alternatives, due to their poor performance, especially, in terms of water‐resistance properties and limited strength 7. Hence the development of efficient adhesives from bioresources is now a challenging field.…”
Section: Introductionmentioning
confidence: 99%